Найдите значение выражения: (3 5/18 m + 2 1/6) * 6 - 7 2/3 m , если m = 3 1/4; m = 1,6.
Найдите значение выражения:
(3 5/18 m + 2 1/6) * 6 - 7 2/3 m , если m = 3 1/4; m = 1,6.
Ответ(ы) на вопрос:
(3 5/18m + 2 1/6) * 6 - 7 2/3m = 12m + 13 1) 3 5/18m * 6 = 59/18m * 6 = 59/3m = 19 2/3m2) 2 1/6 * 6 = 13/6 * 6 = 133) 19 2/3m - 7 2/3m = 12m4) 12m + 13
a) 12m + 13 = 52 при m = 3 1/41) 12 * 3 1/4 = 12 * 13/4 = 3 * 13 = 392) 39 + 13 = 52
б) 12m + 13 = 32,2 при m = 1,61) 12 * 1,6 = 19,2 2) 19,2 + 13 = 32,2
Не нашли ответ?
Похожие вопросы